Grandparent Carers, Child Protection Practice, and the Best Interests of Children: A Case Study. Issue 3 (3rd July 2019) - Gair, Susan; Zuchowski, Ines
ABSTRACT: Increasingly, grandparents are involved in the care of grandchildren, particularly after child safety concerns. Some grandparents, because of changed circumstances, relationships, or decisions made, can experience reduced or lost contact with grandchildren. A recent qualitative, collaborative study explored how relationships between grandparents and their grandchildren could be optimised after child safety concerns. Many grandparents in that study spoke of the frustration of being overlooked in decision-making about their grandchildren, even when they had been providing primary care for the grandchildren. The purpose of this article is to provide a brief background study context, before presenting a case study of one family's ongoing struggles to maintain the children in the grandparents' care. The presented case study has relevance for social work education and training and more widely, for all students and practitioners in the child protection field. IMPLICATIONS: Critical analysis of authentic research case studies can highlight gaps in the implementation of evidence-based practice. Listening to the lived experiences of grandparent carers in interactions with child protection services can contribute to decision-making in the best interests of children through reflective praxis.